HYPOCHOLESTEROLEMIC EFFECT OF GARLIC POWDER IN LAYING HEN: LOW CHOLESTEROL EGG? - Rahardja, D.P.; Hakim, M.R.; Pakiding, W.; Lestari, V.S. (Diponegoro University, 2010)
Forty laying hens Hysex Brown consisting of 2 age groups (27 and 77 weeks of age) were used inthe study to elucidate the hypocholesterolemic effect of garlic powder on egg production, serum and eggcholesterol. They were caged individually and fed diet containing 0 (control), 1, 2, and 4% oven driedgarlic powder for 4 periods of 4 weeks. The old hens consumed more food compared to those of theyoung one, while water consumption was in the reverse condition. The egg production indicated by theyoung hens fed dietary 1 and 2% garlic powder was significantly higher than those fed control diet.However, the old hens produced heavier eggs than those of the young hens, particularly when 1% garlicpowder was supplemented. There was a closed relationship between serum and egg cholesterol, whichreduced gradually with longer time the hens fed dietary garlic. The results clearly demonstrated that thelaying hens fed dietary garlic powder up to 4% produced egg containing lower cholesterol (-34%)compared to those fed control diet; The hypocholesterolemic effect of garlic powder is apparently higherin the old hen compared to that in the young hen.